Strategi Manajemen Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Kinerja Pendidik di MAN 1 Banyuasin Kabupaten Banyuasin: Principal Leadership Management Strategy in Improving the Quality of Educator Performance at MAN 1 Banyuasin, Banyuasin Regency - Elik Shofiyah; Meilia Rosani; Nurlina Nurlina (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study explores the leadership management strategies employed by the principal of MAN 1 Banyuasin in improving the performance quality of educators. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving the principal, teachers, and education staff. The findings reveal that the principal implements the POAC management functions, namely planning, organizing, actuating, and controlling. Planning involves designing work programs and identifying teachers’ needs, while organizing is carried out by delegating tasks according to competencies. Actuating is realized through motivation, training, and mentoring, whereas controlling is conducted via routine supervision and evaluation. Despite these efforts, several challenges remain, including limited funding, administrative workload, and teachers’ varying levels of technological literacy. To address these issues, the principal introduced creative solutions such as optimizing online training, mentoring systems, and adjusting task distribution. The study highlights that a participatory and transformational leadership style fosters collaboration, enhances teacher professionalism, and creates a conducive work culture. However, it also indicates that evaluation mechanisms remain largely administrative and teacher involvement in decision-making is limited, which may restrict innovation. Overall, the findings emphasize that effective leadership strategies not only contribute to teacher performance improvement but also directly enhance the quality of teaching and learning in madrasah-based education. The study further suggests the need for a more holistic, integrative, and participatory leadership model to meet the challenges of dynamic educational reforms.